Reformulation of Juvenile Court: The Perspective of Judicial Amnesty in Indonesia and The Netherlands - Hapsari, Ifahda Pratama; Nurjaya, I Nyoman; Aprilianda, Nurini; Istiqomah, Milda (Faculty of Law, Universitas Pattimura, 2025)
Introduction: This study examines the reformulation of the provisions of Article 70 of Law Number 11 of 2012 concerning Juvenile Criminal Justice through the perspective of the concept of judicial pardon in order to ensure the protection of children's fundamental rights.Purposes of the Research: The research focuses on an in-depth analysis of the concept of rechterlijk pardon as a legal instrument in handling cases of children in conflict with the law.Methods of the Research: The research was conducted using a normative juridical method through a comparative study of the legal systems of Indonesia and the Netherlands.Results of the Research: The research findings indicate that the application of judicial pardon as regulated in Article 70 contains substantial weaknesses, particularly related to the ambiguity of the parameters of